Integration of verbal and nonverbal emotional signals in patients with schizophrenia: Decreased nonverbal dominance. (30th July 2016) - Vogel, Bastian; Brück, Carolin; Jacob, Heike; Eberle, Mark; Wildgruber, Dirk
Abstract: In day-to-day social interaction, emotions are usually expressed by verbal (e.g. spoken words) and nonverbal signals (e.g. facial expressions, prosody). In case of conflicting signals nonverbal signals are perceived as being the more reliable source of information. Deficits in interpreting nonverbal signals – as described for patients with schizophrenic disorders – might interfere with the ability to integrate verbal and nonverbal social cues into a meaningful whole. The aim of this study was to examine how schizophrenic disorders influence the integration of verbal and nonverbal signals. For this purpose short video sequences were presented to 21 patients with schizophrenia and 21 healthy controls. Each sequence showed an actor speaking a short sentence with independently varying emotional connotations at the verbal and the nonverbal level. The participants rated the valence of the speaker's emotional state on a four-point scale (from very negative to very positive). The relative impact of nonverbal cues as compared to verbal cues on these ratings was evaluated. Both groups base their decisions primarily on nonverbal information. However, this effect is significantly less prominent in the patient group. Patients tend to base their decisions less on nonverbal signals and more on verbal information than healthy controls. Highlights: The relative impact of nonverbal cues on judgment of emotional states was evaluated. Videos with independently varying verbal and nonverbal cues were presented. Schizophrenia patients and healthy subjects predominantly relied on nonverbal cues. The impact of nonverbal cues was less intense in patients as compared to controls. The impact of verbal cues was more intense in patients as compared to controls.